Effect of Tempering Temperature on Microstructure and Uniformity of LP Steel Plate under HOP Process. Issue 3 (May 2021) - Xiong, Jie; Tang, Shuai; Wu, Chengyuan; Xu, Ronghui; Sheng, Xinjun; Liu, Zhengyu; Wang, Guodong
Abstract: Longitudinal profiled steel plate ( LP steel plate ) is a green steel product, which is widely used in steel structure fields such as ships and bridges. In this paper, the effect of Heat-treatment Online Process ( HOP ) on microstructure and uniformity of LP steel plate was investigated by thermal simulation test. The results show that the microstructure consists of grain boundary allotriomorphs, upper bainite, acicular ferrite and carbon-enriched austenite at 550°C. During the isothermal process, the austenite transforms into bainite, the acicular ferrite grows and coarsens, and the bainite laths gradually "fuse" to form large granular bainite. After online tempering at 650°C, the austenite transforms into ferrite, acicular ferrite and bainite undergo tempering transformation, in which the size of bainite decreases and some acicular ferrite transforms into polygonal ferrite. After tempering at different temperatures (650∼750°C), the microstructure consists of grain boundary allotriomorphs, coarsened acicular ferrite and a small amount of granular bainite. With the increase of tempering temperature, the tempering transformation degree of acicular ferrite and bainite is intensified. Elongated carbides at grain boundaries become short rods and particles, which decreases the size and aggregation of carbides. Compared with the traditional process, the difference of microstructure and hardness of LP steel plate with different thickness specifications after HOP process is reduced, and the hardness is higher, which is beneficial to improve the performance and uniformity.